2001
DOI: 10.1002/ijc.1222
|View full text |Cite
|
Sign up to set email alerts
|

Effects of human fibroblasts from myelometaplasic and non-myelometaplasic hematopoietic tissues on CD34+ stem cells

Abstract: Fibroblasts demonstrate different phenotypes and functions according to the tissue of origin and its physiopathologic state. We previously showed that fibroblasts isolated in culture from myelometaplasic (MM) spleen differed phenotypically from fibroblasts from normal bone marrow (BM ؉ cells was better in the presence of BM rather than MM spleen-derived fibroblasts. In addition, fibroblasts from MM spleen also induced a differentiation of CD56 ؉ natural killer (NK) cells whereas BM-derived fibroblasts did not.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…However, experimental evidence has accumulated demonstrating that fibroblasts do not act as mere supportive cells but are also able to drive differentiation of other neighboring cell types under both physiologic and pathologic conditions (19,20). Especially in the human hemopoietic system (3,21) it has been shown that homogeneous stromal fibroblast populations established in culture from bone marrow were able to directly contribute to the formation of blood cells from all lineages except T/NK lymphocytes, with a majority of granulomonocytes. The results presented in this work clearly show that fibroblasts isolated from human spleen also regulate blood cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, experimental evidence has accumulated demonstrating that fibroblasts do not act as mere supportive cells but are also able to drive differentiation of other neighboring cell types under both physiologic and pathologic conditions (19,20). Especially in the human hemopoietic system (3,21) it has been shown that homogeneous stromal fibroblast populations established in culture from bone marrow were able to directly contribute to the formation of blood cells from all lineages except T/NK lymphocytes, with a majority of granulomonocytes. The results presented in this work clearly show that fibroblasts isolated from human spleen also regulate blood cell differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…The constitutive expression of IL-15 on the surface of human spleen-derived fibroblasts was quite striking because stromal fibroblasts isolated from other tissue sources did not show such expression unless stimulated by inflammatory cytokines or derived from pathologic lesions (3,26). In contrast, blood-derived cells, including monocytes, monoblastoid cells, and leukemic progenitors, have been reported to constitutively express membrane-associated IL-15 without any IL-15 secretion (27)(28)(29).…”
Section: Discussionmentioning
confidence: 99%
“…This constitutes a feedback loop that favors the persistence of the inflammatory process in RA. Interestingly, RASFibs share constitutive surface expression of IL-15 with human spleen-derived fibroblasts (19), whereas OASFibs and fibroblasts from other locations do not demonstrate surface IL-15 unless stimulated by inflammatory cytokines (20) or derived from tumor stroma (36). In contrast, fibroblasts from all sources do constitutively express intracellular IL-15 (15).…”
Section: Discussionmentioning
confidence: 99%
“…This hypothesis is based on the fact that human spleen-derived but not bone marrow-derived myofibroblasts constitutively express a mb-IL-15 (spleen myofibroblast [SMF] membrane-bound [mb]-IL-15) necessary and sufficient to trigger, upon coculture, the differentiation of circulating (but not BM) CD34 ϩ progenitors into functional NK cells. [16][17] The way IL-15 is anchored to the cell membrane seems to have a major effect on its presentation in trans and on its effects on target cells. [4][5][6][7][10][11][18][19] For these reasons, we investigated (1) the mechanism of anchorage of SMFmb-IL-15 at the cell membrane; (2) the type of signal transduction triggered upon contact with normal and leukemic hematopoietic CD34 ϩ cells; and (3) the biologic effects of SMFmb-IL-15 on leukemic cells.…”
Section: Introductionmentioning
confidence: 99%